Analisis Pengembalian Dana (refund) pada Pemutusan Akad Asuransi Syariah di Tengah masa kontrak - Dede San San Ramlan sandiyana; Mochamad Syahril Sabar Suryana; Agung Ikram Gunawan; Rubby Aziz Zaura Kamal; Raihani Fauziah (CV. ITTC INDONESIA, 2025)
This study explores the refund mechanism in Islamic insurance (takaful), particularly in cases of contract termination prior to maturity. Rooted in the principles of justice, mutual assistance (ta’awun), and collective guarantee (takaful), Islamic insurance avoids elements of riba, gharar, and maisir through a combination of tabarru’ (donation) and tijarah (commercial) contracts. Although Fatwa DSN-MUI No. 21/DSN-MUI/X/2001 stipulates that tabarru’ funds are irrevocable donations, refund practices often raise legal uncertainties due to the absence of standardized procedures and clear contractual provisions. Fatwa DSN-MUI No. 81/DSN-MUI/III/2011 allows for refund agreements, yet implementation varies across institutions. A case study of PT Sun Life Syariah is employed to examine refund practices in mid-contract termination, focusing on contract structure, transparency, and regulatory compliance. Using a normative approach and empirical analysis of policy documents, internal SOPs, and stakeholder interviews, this research aims to propose a refund mechanism aligned with maqashid sharia and Indonesian positive law. The findings are expected to enrich the academic discourse in Islamic economic law and contribute to consumer protection reform in the Islamic insurance industry.